Existence of Global Solutions for Nonlinear Magnetohydrodynamics with Finite Larmor Radius Corrections - Fariha Elsrrawi; Harumi Hattori (International Journal of Differential Equations)
We discuss the existence of global solutions to the magnetohydrodynamics (MHD) equations, where the effects of finite Larmor radius corrections are taken into account. Unlike the usual MHD, the pressure is a tensor and it depends on not only the density but also the magnetic field. We show the existence of global solutions by the energy methods. Our techniques of proof are based on the existence of local solution by semigroups theory and a priori estimate.